Public speaking training for students of Madrasah Aliyah ‘Aisyiyah Sungguminasa - Wardah Wardah; Muhammad Yahya; Syukri Syukri; Arni Arni; Lukman Lukman; Fitri Natalia; Zahra Adelia Sari (Universitas Muhammadiyah Magelang, 2024)
In an increasingly interconnected world, public speaking skills are essential for high school students. These skills foster effective communication, build self-confidence, and prepare students for future challenges. This community service project aimed to enhance public speaking abilities among students at Madrasah Aliyah ‘Aisyiyah Sungguminasa. An audience-centered approach was employed, incorporating five stages: pre-presentation, early evaluation, orientation, post-presentation, and feedback. Forty-seven students actively participated in the training. While participants demonstrated increased basic public speaking knowledge and skills, mastering public speaking theory and practice required further development. Challenges included public speaking anxiety and technical difficulties, yet participants exhibited improved body language during the second presentation.